Pemberdayaan Santripreneur di Pesantren: Kajian Kepemimpinan Perempuan (Nyai) dalam Meningkatkan Keterlibatan Santriwati dalam Berwirausaha - Pratiwi, Ratih; Wardhani, Windi Novia Ratri; Prabowo, Shidqon; Amaniyah, Farikhah; Rohim, Fatkhur (Jurnal Iqtisaduna, 2022)
Pesantren is basically an institution that plays a very important role in the era of globalization, namely shaping one’s personality. Character education in the current era of globalization really needs character education, because the purpose of character education is to expand spiritual intelligence. The biggest challenge in facing globalization and modernization is where the empowerment of human resources (HR) and the economy in life has changed in every way, especially social and socio-cultural which is very fast and fundamental in every aspect of life. Islamic boarding schools must be able to create people who are IMTAQ (faithful and pious), who are knowledgeable and charitable and form modern humans who are sensitive to contemporary social realities such as "al muhafadotu ’ala qodimish sholih wal akhdu bi Jadidil Ashlah" (maintaining good old things and taking matters into account). For this reason, several strategic steps need to be taken, namely: knowledge, entrepreneurial spirit and work ethic/independence. Islamic boarding schools have developed and won the trust of the community through the implementation of a dormitory system that allows students to receive religious guidance using a reading system or madrasa. In addition to showing the level of diversity, orientation of the pesantren leadership and the independence of the kiai, the high number of Islamic boarding schools indicates that pesantren is a private educational institution that is very independent and is actually a community-based educational practice. The typical leadership of Nyai has a very broad influence on the development of pesantren in society. Based on the analysis of the situation, it is necessary to have an effort to provide alternative solutions that can increase the entrepreneurial involvement of female students through the leadership of Nyai in Islamic Boarding Schools in Semarang City.